Some Aspects Of The Biology And Control Of Quadriacanthus Kobiensis Ha Ky, 1968 (Monogenea: Dactylogyridae) From Clarias Batrachus (Linnaeus) In Indonesia - Kamarudin, Oman (1989)
This study covered some aspects of the biology and control of monogenetic trematode from walking cat fish Clarias batrachus (L innaeus ) . The monogenetic trematode from walking catfish at Wirya Mina Fish Farm , Depok , Bogor, Indonesia was identified as Quadriacanthus kobiensis Ha Ky, 1968.Three levels of infection with Q . kobiensis were established in C . batrachus to study its effect on growth rate . The mean number o f parasite for the three treatments were: l ow 12.2, medium 12.8 and high 187.3 . Results of the effect of this parasite on walking cat fish Clarias batrachus showed that the specific growth rate at all levels of infection: l ow , medium and high were significantly lower than the control . This parasite can reduce the specific growth rate of walking cat fish by 52 . 9% as compared to the control . There was no significant difference of the specific growth rates amongst fish with high , medium and low levels of infection . No significant difference was seen in the mortality rate at these levels of infection when compared with the control .